1984
DOI: 10.1007/bf01400857
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anterior approach to cervical discs review of 60 consecutive cases of discectomy without fusion

Abstract: During the past six years 60 patients have undergone anterior cervical microsurgical discectomy without exogenous intercorporal grafting using the operating microscope. This alternative method of treatment is a further refinement of previous techniques for the removal of cervical disc protrusions, which fulfils all the criteria of effective surgery. Discectomy provides ample exposure of the neural elements through the disc space. The visualisation of the underlying pathology is adequate through direct light an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
4

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 31 publications
0
22
0
4
Order By: Relevance
“…10,26,36 Whether patients develop symptoms may depend on time of follow-up. 10,25 Whether this is related to the different design of the cages is unknown and needs further investigation. 3 As the range of motion varies in different types of cages, this not only has influence on the primary cervical stability but also on the subsidence.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…10,26,36 Whether patients develop symptoms may depend on time of follow-up. 10,25 Whether this is related to the different design of the cages is unknown and needs further investigation. 3 As the range of motion varies in different types of cages, this not only has influence on the primary cervical stability but also on the subsidence.…”
Section: Discussionmentioning
confidence: 96%
“…2,6,13 Prior to the introduction of ACDF using PCTC or bone graft, ACD was routinely performed in our department. Husag et al 25 reported the results of 60 patients undergoing microsurgical ACD during a 6-year period in our institution. The authors reported an excellent overall benefit in 95% of the patients after 6 and 12 months with a lower incidence of complications compared to previous series.…”
Section: Discussionmentioning
confidence: 98%
“…Many surgeons do not interpose a graft into the empty intervertebral disc space [2,7,11]. In our opinion, this procedure is unsafe and not advisable because of the danger of subsequent kyphosis of the cervical spine [2,6], especially if the uncinate processes are resected for adequate nerve root decompression.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no real consensus on the useif at all [2,7,11 ] -of autologous [6,7,9,11,12], heterologous [16,17] or alloplastic materials [3,5,10,13,14] for the disc space graft for ventral fusion, the goal of which is either solid ossification or at least osseous fit. There is no doubt that autogenous iliac bone graft, with all the well-known disadvantages, is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Many theories have been formulated since then, most of which implicate hematoma as the main cause of bone formation and subsequent fusion, as well as injuries of the soft tissues or the coexistence of a fracture. Spontaneous traumatic fusion has been associated with the type of injury (4,6,9,10,13,15), immobilization (3,8), and soft-tissue distraction (2,3). The mechanism of injury was also associated with spontaneous fusion (2).…”
mentioning
confidence: 94%